The effects of habitat size and isolation on wetland benthos - Barnes, Karen (My University, 1993)
I investigated the effects of habitat fragmentation in terms of spatial scale (enclosures of different sizes) and the degree of isolation (different mesh sizes) on benthic macroinvertebrates in the littoral zone of a shallow lake. I hypothesized that decreasing diversity and increasing temporal variation will occur with decreasing size and increasing isolation of enclosures. This hypothesis was tested by examining spatial and temporal variation (coefficient of variation) among replicate enclosures. Variation in benthic diversity was further examined within and among enclosures. The degree of isolation and habitat size interacted to determine variation of species abundance in the benthic community. Specifically, at higher levels of isolation (plastic enclosures), variance among enclosures of the same and of different sizes was the greatest compared to less isolated enclosures. We also investigated the persistence of benthic macroinvertebrates where persistence is defined as constancy in the number of organisms through time. We hypothesized that persistence is lower in small and more isolated enclosures as opposed to large less isolated ones. We simultaneously tested the hierarchical nature of community persistence as outlined by Rahel (1990) to determine if there is a difference in the assessment of persistence of the assemblage depending on the analytical scale used. There is a possible scale effect at the level of abundance rank since small (1 and 4 m2 ) enclosures had lower persistence than large (9 and 16m2 ) enclosures. Low persistence in both abundance and abundance rank over time prevented a conclusive test of the hierarchical nature of community persistence. I conclude that it is important for benthic enclosure experiments to be conducted at various spatial and analytical scales and that, where replication is possible, spatial and temporal variation allows a thorough examination of different community responses.
Keywords: habitat size; wetland; isolation; benthos